2021
DOI: 10.1111/jcpe.13564
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive benefits of systemic metronidazole on non‐surgical treatment of peri‐implantitis. A randomized placebo‐controlled clinical trial

Abstract: Aim To study clinical, radiographic, and microbiological outcomes after non‐surgical therapy of peri‐implantitis with or without adjunctive systemic metronidazole. Materials and Methods A randomized placebo‐controlled clinical trial was carried out in 32 subjects (62 implants) diagnosed with peri‐implantitis. Implants received a mechanical non‐surgical debridement session and systemic metronidazole or placebo. Clinical, radiographic, and microbiological outcomes were evaluated at baseline, 3, 6, and 12 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
134
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(137 citation statements)
references
References 39 publications
1
134
0
2
Order By: Relevance
“…Thirdly, the importance of giving the patient a course of antibiotics in order to eliminate the aerobic and anaerobic microbes that may activate in cases of periosteal injuries [ 1 , 5 , 28 ]. Fourth, emphasizing to the patient the importance of adherence to the postoperative instructions [ 28 , 29 , 30 ]. By following these steps and adopting them in dental clinics, the chances of developing alveolitis and infection can be reduced to the minimum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirdly, the importance of giving the patient a course of antibiotics in order to eliminate the aerobic and anaerobic microbes that may activate in cases of periosteal injuries [ 1 , 5 , 28 ]. Fourth, emphasizing to the patient the importance of adherence to the postoperative instructions [ 28 , 29 , 30 ]. By following these steps and adopting them in dental clinics, the chances of developing alveolitis and infection can be reduced to the minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Clavulanic acid is irreversible inhibitor of β-lactamase enzymes, well absorbed orally, and combined with amoxicillin [ 1 , 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotic prophylaxis, especially that based on a mix of amoxicillin and metronidazole, is widely used by clinicians for the treatment of peri-implantitis with excellent results [ 37 ], and in a retrospective clinical study, it has been shown to have superior results in terms of BoP and mucosal recession compared to the group of patients who did not receive systemic antibiotics [ 38 ]. Moreover, in a randomized clinical trial, the use of systemic metronidazole elicited excellent results in clinical, radiographic, and microbiological parameters in the non-surgical treatment of peri-implantitis [ 39 ]. The vitamin supplement has been shown, both in vitro and in clinical studies, to be a very useful support in the healing of surgical wounds [ 40 ]; moreover, a retrospective clinical study has shown how the vitamin supplement has proved useful in countering antibiotic-associated pseudomembranous colitis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%